17 Comparing Natural Vegetation and Food Plot Preference against Supplemental Protein Pellets in Captive White-tailed Deer (Odocoileus virginianus) and Exotic Species. (28th November 2020) - McQueen, Robert W; Beverly, Marcy M; Kelley, Stanley F; Anderson, Mark
Abstract: Supplemental feed is the most expensive input in the captive wildlife industries. This is due to operations utilizing high-energy pellets as supplemental feed. Low fence operations often utilize food plots with high quality vegetation to minimize cost and increase forage availability for wildlife. The objective of this study was to determine forage preference of animals in captivity, and determine the most cost effective method of supplemental feeding. Seven food plots covering 25 acres contained one of three treatments. The treatments were: a commercial blend of soybeans; a commercial blend of soybeans, sunflowers, and milo; native/unplanted. Three utilization cages were set up to inhibit wildlife access to samples within each food plot to act as a control. Height of vegetative samples, inside and outside of the utilization cages, was collected on days 30, 60, and 90 after planting. The 30-d sample showed a preference of native/unplanted vegetation over the commercial treatments, P < 0.05. However, samples taken on days 60 and 90 showed the preference shifted toward the commercial blends, P < 0.05. This browsing preference indicates stage of maturity had an impact on plant selection. Regardless of sample date, the commercial blends showed a difference of P < 0.01, selecting the soybean blend more frequently. With an increased selection of the forages in the food plots, there was a decrease in cost of purchasing feed pellets with a total savings of approximately $5, 500.00 from April 5-July 5, 2019. These results suggest that white-tailed deer and exotic species in captivity prefer forages compared to pelleted feed. Supplemental feeding programs that include food plots could allow for natural feeding tendencies, while being more cost effective for operations in the captive wildlife industries.